The Implementation of "Listen English Daily Practice" Application in Learning Listening Comprehension - Nurhidayat, Afinka Ramandani; Masrupi, Masrupi; Rima, Rosmania (Journal of Linguistics, Literacy, and Pedagogy, 2023)
The objectives of this research were to describe the implementation of Listen English Daily Practice in learning listening comprehension and to find out the students' responses in using the application. This research employed descriptive qualitative research, conducted at SMA Islam Al-Layyinah. The data was obtained from the observation, interviews, and documentation. The findings show that the implementation of application was carried out in three stages of followed the pre-listening, while-listening, and post-listening phases. The application was uesful to assist the students in learning listening comprehension in the classroom. Moreover, the application helped the students to enhance their listening comprehension ability. Apart from that, the use of the applications received positive feedback from the learners as the suggested that the application provided the familiar topics, interesting features of the app, joyful learning process, and easy to use.